Pengaruh Kualitas Produk dan Kualitas Pelayanan terhadap Kepuasan Konsumen Botania Coffee & Eatery - Amanda Siska Sulistiowati; Salma Rahamawati; Muhammad Ilyas S; Rudi Mahendra; Marjam Desma Rahadhini (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
This research aims to look at Product Quality and Service Quality on Customer Satisfaction at Botania Coffee & Eatery. The background of this study is based on the increasingly tight competition in the food and beverage industry, especially in the coffee & eatery segment which has experienced significant growth. In these conditions, product and service quality are key factors in attracting and retaining customers. The research method used is a quantitative method with a causal approach, where data is collected by distributing questionnaires to consumers who have visited and enjoyed services at Botania Coffee & Eatery. The sample used in this was 30 respondents. The data that has beenobtainned are processed using multiple linear regressionanalysis to determine the extent to which the independent variables (product quality and service quality) influence the dependent variable (customer satisfaction). The expected results of this study are a positive and significant effect of product quality and service quality on customer satisfaction.